Rotational Velocities for the Brighter A-Type Stars - Abt, Helmut A. (1993)
In 1968 van den Heuvel showed that the rotational velocities at many A types have peaks below V sin i = 45 km s⁻¹ and above 90 km s⁻¹. We explored this bimodal behavior by obtaining new rotational velocities of 1761 A-type stars with coudé CCD spectra and, to date, new MK classifications for 956 of those. We find that the slow rotators consist of Ap, Am, and short-period binaries while the rapid rotators are normal and λ Bootis stars. The overlap is only 8–10% and can probably be attributed to undetected abnormal stars and binaries. The λ Bootis stars discovered purely by their having weak λ4481 Mg II constitute about 18% of the early A-type stars but 4% at the late ones. Statistically all such λ Bootis stars have V > 100 km s⁻¹ but they constitute only a small fraction of those stars. More than half of the stars classified as A2 IV (and some at Al IV and A3 IV) seem to be a hitherto unrecognized class of slowly-rotating abnormal-abundance stars of luminosities like those of class V stars.